PENGARUH PENAMBAHAN TEPUNG KEONG MAS (Pomacea canaliculata) PADA PAKAN KOMERSIL TERHADAP PERTUMBUHAN BENIH IKAN LELE DUMBO (Clarias gariepinus) - Giffari Mohammad Saragih; Eri Yusni (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
Dumbo fish are economically valuable fish, consumer demand is high enough, but not yet accompanied by intensive and optimal effort. One attempt to overcome this problem by substituting commercial feed with Golden Snail flour which has a high enough protein content as a protein. This study aims to determine the effect of flour on commercial feed on the growth of dumbo fish seeds. Fish is a 5-6 cm dumbo fish kept in size of 45x20x20 cm as many as 9 units arranged randomly. The research design was carried out with three parts: P4K0 (100% commercial feed), P3K1 (75% commercial feed + 25% conch flour), and P2K2 (50% commercial feed + 50% conch flour). The results showed that the golden snail flour can be used as substitution in fish feed, where the best yielding feed is P2K2 (commercial feed 50% + mas 50% cloves) with the length of 3.16 cm and weight 6.71 g, with a value of Conversion ratio of 1.22 and an 80% lifetime value.Keywords: Clarias gariepinus, Golden Snail Flour, Growth, Feed Conversion Rate, Survival Rate